Linking Smart-Phone Addiction to Self-Concept Clarity Among Chinese College Students: The Chain Mediation Roles of Social Anxiety and Social Withdrawal. - Wang, Xu; Niu, Jinpeng (Inquiry (00469580), 2026)
In digital era, the self-concept clarity of college students is increasingly alarming in Chinese educational system. In view of this, the current study investigated the structural associations between smart-phone addiction, social anxiety, social withdrawal, and self-concept clarity among Chinese college students. A chain mediation model was employed in statistical analysis, and the participants were 891 college students selected from 2 universities in Shandong, China. The findings demonstrated that smart-phone addiction can not only directly and negatively influence self-concept clarity, but also indirectly and negatively affect self-concept clarity through the single mediation of social withdrawal as well as the chain mediation of social anxiety and social withdrawal. Besides, although the direct associations between smart-phone addiction and social anxiety and between social anxiety and self-concept clarity were significant, the indirect effect of smart-phone addiction on self-concept clarity via social anxiety was insignificant. Smart-phone addiction may lead to social anxiety and social withdrawal, whereby impairing the self-concept clarity of Chinese college students.